T | true if an event had a hit in the tagger, false otherwise |
R | true if an event passed the recoil trigger, false otherwise |
C | true if an event had a hit in the CPV, false otherwise |
[A] | the total number of events satisfying logical condition A |
!A | the logical NOT of event A |
A == B | statement that events satisfying condition A are the same as those satisfying condition B |
A =~ B | statement that events satisfying condition A are statistically typical of those satisfying condition B but the sets are not necessarily equal (this implies [A] = [B]) |
A.B | logical AND of conditions A and B for the same event |
A|B | logical OR of conditions A and B for the same event |
A&B | true for some event a if A is true for that event and, within some well-defined time interval that contains a, there exists at least one event for which B is true |
A*B | true for some event a if A is true for that event and, within some well-defined time interval which excludes a, there exists at least one event for which B is true |
What do we want? [R.T.!C] What do we measure directly? only coincidence counts, such as [R&T], [T*C] and the like So what are these counters in the ntuple? coint() = [R&T] coina() = [R*T] vetot() = [(R&T).!(R&C)] vetoa() = [(R*T).!(R&C)] What is the claim in the paper? [R.T.!C] = [(R&T).!(R&C] - [(R*T).!(R&C)] Proof: axiom 0: A.A == A axiom 1: A.B == B.A axiom 2: A*B =~ B*A axiom 3: (A.B).C = A.(B.C) = (A.C).B theorem 1: A&B =~ (A.B)|(A*B) This is a consequence of the independence of different events and the fact that they are randomly and uniformly distributed in time. It states that the only way for an event to satisfy A&B is either for the event to satisfy A.B or for it to satisfy A and to be found in random coincidence with a second event which satisfies B. Any random interval which excludes the first event may be used to evaluate the condition A*B, with the caveat that if A or B themselves contain a * operator in their definition then each * found in the composite expression must be evaluated on a different random interval. theorem 2: [A&B] = [A.B] + [A*B] - [(A.B).(A*B)] This is a general theorem from set theory. The caveat explained above under theorem 1 regarding repeated use of the * operator in any logical expression applies here as well. [R.T.!C] = [(R.T).!C] = [(R.!C).T] = [(R.!C)&T] - [(R.!C)*T] + [((R.!C).T).(R.!C)*T))] = [(R.!C).(R&T)] - [(R.!C).(R*T)] + [((R.!C).T).(R.!C)*T))] The first term in this expression [(R.!C).(R&T)] = [R&T] - [(R.C).(R&T)] The last term in this expression [(R.C).(R&T)] = [(R&C).(R&T)] - [(R*C).(R&T)] + [(R.C).(R*C).(R&T)] Putting these results together gives [R.T.!C] = [R&T] - [(R&C).(R&T)] + [(R*C).(R&T)] - [(R.C).(R*C).(R&T)] - [(R.!C).(R*T)] + [((R.!C).T).(R.!C)*T))] = [(R&T).!(R&C)] - [(R.!C).(R*T)] + [(R*C).(R&T)] - [(R.C).(R*C).(R&T)] + [((R.!C).T).(R.!C)*T))] Now the second term in this expression [(R.!C).(R*T)] = [R*T] - [(R.C).(R*T)] The last term in this expression [(R.C).(R*T)] = [(R&C).(R*T)] - [(R*C).(R*T)] + [(R.C).(R*C).(R*T)] Putting these results together gives [R.T.!C] = [(R&T).!(R&C)] - ([R*T] - [(R&C).(R*T)]) - [(R*C).(R*T)] + [(R.C).(R*C).(R*T)] + [(R*C).(R&T)] - [(R.C).(R*C).(R&T)] + [((R.!C).T).(R.!C)*T))] = [(R&T).!(R&C)] - [(R*T).!(R&C)] - [(R*C).(R*T)] + [(R*C).(R&T)] - [(R*C).(R.C).(R&T)] + [(R*C).(R.C).(R*T)] + [((R.!C).T).(R.!C)*T))] [A.(R.C).(R*C)] = [A.(R&C).(R*C)] - [A.(R*C).(R*C)] + [A.(R.C).(R*C).(R*C)] = [A.(R&C).(R*C)] - [A.(R*C)^2] + [A.(R&C).(R*C)^2] - [A.(R*C)^3] + [A.(R&C).(R*C)^3] - [A.(R*C)^4] + ... = [A.(R&C).(R*C)] - [A.!(R&C).(R*C)^2] - [A.!(R&C).(R*C)^3] - ... Combining this with the above results gives [R.T.!C] = [(R&T).!(R&C)] - [(R*T).!(R&C)] - [(R*C).(R*T)] + [(R*C).(R&T)] - [(R&T).(R&C).(R*C)] + [(R&T).!(R&C).(R*C)^2] + [(R&T).!(R&C).(R*C)^3] + ... + [(R*T).(R&C).(R*C)] - [(R*T).!(R&C).(R*C)^2] - [(R*T).!(R&C).(R*C)^3] - ... + [((R.!C).T).(R.!C)*T))] = [(R&T).!(R&C)] - [(R*T).!(R&C)] + [(R&T).!(R&C).(R*C)] + [(R&T).!(R&C).(R*C)^2] + [(R&T).!(R&C).(R*C)^3] + ... - [(R*T).!(R&C).(R*C)] - [(R*T).!(R&C).(R*C)^2] - [(R*T).!(R&C).(R*C)^3] - ... + [((R.!C).T).(R.!C)*T))] = [(R&T).!(R&C)] + [(R&T).!(R&C).(R*C)^1] + [(R&T).!(R&C).(R*C)^2] + [(R&T).!(R&C).(R*C)^3] + ... - [(R*T).!(R&C)] - [(R*T).!(R&C).(R*C)^1] - [(R*T).!(R&C).(R*C)^2] - [(R*T).!(R&C).(R*C)^3] - ... + [((R.!C).T).(R.!C)*T))] But for any condition A, [A.R.(R*C)^N] = [A.R]*fC^N where N is any integer and fC is just a universal constant which depends on [C] and the gate width implicit in the * operator. Note that fC lies in the interval [0,1]. Substitution into the above expression gives [R.T.!C] = ( [(R&T.!(R&C)] - [(R*T).!(R&C] ) / (1-fC) + [(R.T).!(R.C).(R*T)] So there are two corrections to the claim in the paper. First of all there is the overall normalization factor in the leading term, which is of order 5/3. Secondly there is the second term which must be included. For any expression A the following relation holds: [A.(R.T)] = [A.(R&T)] - [A.(R*T)] + [A.(R.T).(R*T)] = [A.(R&T)] - [A.(R*T)] + [A.(R&T).(R*T)] - [A.(R*T)^2] + [A.(R&T).(R*T)^2] - [A.(R*T)^3] + ... = [A.(R&T)] - [A.!(R&T).(R*T)^1] - [A.!(R&T).(R*T)^2] - ... = [A] - [A.!(R&T).(R*T)^0] - [A.!(R&T).(R*T)^1] - ... = [A] - [A.!(R&T)] / (1-fT) This implies for the second term above [(R.T).!(R.C).(R*T)] = [(R.T).(R*T)] - [(R.T).(R.C).(R*T)] = [R*T] - [(R*T).!(R&T)]/(1-fT) - [(R.C).(R*T)] + [(R.C).(R*T).!(R&T)]/(1-fT) = [R*T] - [(R*T).!(R&T)]/(1-fT) - [R*T] + [(R*T).!(R&C)]/(1-fC) + [(R*T).!(R&T)]/(1-fT) - [(R*T).!(R&T).!(R&C)]/((1-fC)*(1-fT)) = [(R*T).!(R&C)]/(1-fC) - [(R*T).!(R&T).!(R&C)]/((1-fC)*(1-fT)) Finally this leads to [R.T.!C] = ( [(R&T.!(R&C)] - [(R*T).!(R&C] ) / (1-fC) + [(R*T).!(R&C)]/(1-fC) - [(R*T).!(R&T).!(R&C)]/((1-fC)*(1-fT)) = [(R&T.!(R&C)]/(1-fC) - [(R*T).!(R&T).!(R&C)]/((1-fC)*(1-fT))
This is the result we have been looking for. The factor fT is only a few percent for an individual tagger channel, and !(R&T) is approximately equivalent to the factor (1-fT) so the principal difference between the last equation and the original result
[(R&T).!(R&C)] - [(R*T).!(R&C)]is only in the overal scale factor 1/(1-fC). This does not change the shape of spectra, so for most purposes it is irrelevant.